0970 Resident Physician Work Hours Decreased and Sleep Duration Increased Following Elimination of Scheduled Extended Duration Shifts. (12th April 2019) - Barger, Laura K; Sullivan, Jason P; Blackwell, Terri; O'Brien, Conor S; Hilaire, Melissa A St; Rahman, Shadab; Phillips, K J K; Qadri, Salim; Wright, Kenneth P; Lockley, Steven W; Landrigan, Christopher P; Stone, Katie L; et al.
Abstract: Introduction: Extended-duration work shifts (≥ 24 hours), the cornerstone of medical education, have been associated with reduced sleep first-year resident physicians in a single-site study. We compared more senior resident physician work hours and sleep habits in a multi-center clustered-randomized crossover clinical trial that randomized resident physicians to an Extended Duration Work Roster (EDWR) with extended-duration (≥24 hours) shifts or a Rapidly Cycling Work Roster (RCWR) where scheduled shift lengths were limited to no more than 16 consecutive hours. Methods: Across six U.S. academic medical centers, we enrolled 302 resident physicians in their second or more senior postgraduate year. They completed 370 one-month pediatric intensive care unit rotations. Sleep was objectively estimated with wrist-worn actigraphs. Work hours and subjective sleep duration were reported in an electronic daily diary. Results: Resident physicians work hours were reduced by 10% during the RCWR (61.9 ± 4.8 hours compared to 68.4 ± 7.4 hours during the EDWR; p<0.0001). During the RCWR, 73% of work hours occurred within shifts of ≤16 consecutive hours. In contrast, during the EDWR 38% of work hours occurred on shifts of ≤16 consecutive hours. Resident physicians obtained significantly more sleep per week on the RCWR (52.9 ± 6.0 hours) compared to the EDWR (49.1 ± 5.8 hours, p<0.0001). The percentage of 24-hour intervals with less than 4 hours of actigraphically measured sleep was 9% on the RCWR and 25% on the EDWR (p<0.0001). During the RCWR, 4% of work hours were preceded by two or fewer hours of sleep in the preceding 24 hours, as compared to 10% of work hours during the EDWR (p<0.0001). Conclusion: RCWRs were effective in reducing weekly work hours and the occurrence of >16 consecutive hour shifts in more senior resident physicians. Sleep duration was increased and resident physicians were more rested while caring for patients. Additional research is needed to optimize scheduling practices that ensure sufficient sleep prior to all work shifts. Support (If Any): ROSTERS supported by National Heart, Lung, and Blood Institute (U01-HL-111478, U01-HL-111691).